Evaluation of the effectiveness of three sticky traps to monitor four species of cockroaches (Hexapoda: Blattaria) with simulated use tests - Drago, A.; Montarsi, F.; Dutto, M.; Martini, S.; Vitale, M. L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Cockroaches are the pest of major concern for the disinfestation programs of the sanitary system in Italy. Hygienic-sanitary interest is linked to the role of mechanical vectors of pathogens and to their allergological potential. Sticky traps are the best tool to monitor the presence of these insects and several types of them are available on the market. In most of the cases the traps are not indicated for a given species, but, instead, generically for cockroaches. Domestic cockroaches differ in morphology, size and habits. Consequently, the effectiveness of the trap can change in relation to the target species. Materials and methods. In this study three of the most employed traps in Italy were compared: the INDIA trap with and without its attractant tablet (hereafter mentioned as INDIA-A and INDIA-E, respectively), the ZAPI Simply trap and the CATCHMASTER Spider & Insect Glue trap. We chose the four most common species of cockroach (Blattodea) in Italy, Blatta orientalis (L.), Periplaneta americana (L.) (Blattidae), Blattella germanica (L.) and Supella longipalpa (F.) (Blattellidae). Each species of cockroach was tested separately inside arenas containing one of the traps. Each test (one species with one kind of trap) was replicated five times. Results and discussion. The INDIA-A trap collected more cockroaches of every species, followed by the INDIA-E. The ZAPI trap caught less specimens of each species in respect to the INDIA traps, with the only exception of B. orientalis, for which the ZAPI trap caught more than the INDIA-E. The CATCHMASTER trap performed significantly less for all the species. B. orientalis was the species most abundantly caught by all traps, followed by B. germanica, S. longipalpa and P. americana. No significant difference was observed in the catch according to the developmental stage. In general, there was no particular predisposition of any trap to catch a particular species. Conclusions. It is not possible to indicate a model of trap for each species of cockroach, but it is clear that different traps have different performances in terms of attractiveness and capture. Therefore, the choice of the trap affects the results of the monitoring, and as consequence, the evaluation of the infesting population of the pest.